Ecology of geckos in edible bird nest swiftlet Aerodramus fuciphagus ranch - Mohd Azmi, Siti Fatimah (2017)
Swiftlet farming industry is an emerging industry due to high demand and prices. Malaysia is one of the leading country in this industry. Although it is a profitable industry, there are also many problems and challenges faced by the farmers that goes into the industry. This research is done to study on the pests in swiftlet ranch, specifically geckos. Research swiftlet ranch in UPM is still new. It was established in 2015 so it was just about a year and few months there. Not so many birds are going in and out or colonizing the ranch yet. Until now, it was recorded about 4 birds are entering the ranch and only 2 edible bird nest are found in the ranch. Based on the research, the main species of geckos inhabiting the swiftlet ranch is Hemidactylus frenatus and Hemidactylus parvimaculatus. It was found that most of the lizards are feeding on the insects. These insects are attracted to the light that is automatically on during night. It was no sign of geckos preying on nestlings or eating the nest. The birds are not having any nestling yet since it is not in the mating season. Geckos are found to be active throughout the day. There is presence of geckos in every hour but it is the highest during early morning around 5 a.m. to 6 a.m. and also late evening from 6 p.m. to 7 p.m.